2019
DOI: 10.1007/s00787-019-01420-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and satisfaction of children, young people and their parents with alternative mental health models to inpatient settings: a systematic review

Abstract: Community-based mental health services for children and young people (CYP) can offer alternatives to inpatient settings and treat CYP in less restrictive environments. However, there has been limited implementation of such alternative models, and their efficacy is still inconclusive. Notably, little is known of the experiences of CYP and their parents with these alternative models and their level of satisfaction with the care provided. Therefore, the main aim of this review was to understand those experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…MMAT does not recommend assigning a single score based on the assessment [ 21 ]. However, in this review, we used a specific metric derived from a previous study [ 22 ]. To rate the quality of each of the studies to justify the reasons for the final inclusions and exclusions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMAT does not recommend assigning a single score based on the assessment [ 21 ]. However, in this review, we used a specific metric derived from a previous study [ 22 ]. To rate the quality of each of the studies to justify the reasons for the final inclusions and exclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were classified as high, medium, or low quality, depending on the number of criteria that were met. A study was considered high quality if all 5 MMAT criteria were met, medium if 3 or 4 criteria were met, and low when a study met 1 or 2 criteria [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, accumulating research in children and adolescents support the utilization of models of intervention during crisis that are implemented early and prevent the escalation of mental health issues through community-based approaches [ 23 ]. However, most of the recently published brief interventions are aimed at specific psychiatric emergencies, such as suicidality [ 8 , 24 ] and trauma exposure [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, a systematic review (Shepperd et al, 2009) identified eight worldwide commonly used alternative models to inpatient care for young people with complex mental health needs, such as multisystemic therapy, day hospitals and intensive specialist outpatient service. However, a more recent review reported high levels of parental burden and complex emotional reactions associated with engagement with such alternative interventions (Vusio et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%